DNAzymes, Novel Therapeutic Agents in Cancer Therapy: A Review of Concepts to Applications. (1st November 2021) - Thomas, I. B. K.; Gaminda, K. A. P.; Jayasinghe, C. D.; Abeysinghe, D. T.; Senthilnithy, R.
Abstract : The past few decades have witnessed a rapid evolution in cancer drug research which is aimed at developing active biological interventions to regulate cancer-specific molecular targets. Nucleic acid-based therapeutics, including ribozymes, antisense oligonucleotides, small interference RNA (siRNA), aptamer, and DNAzymes, have emerged as promising candidates regulating cancer-specific genes at either the transcriptional or posttranscriptional level. Gene-specific catalytic DNA molecules, or DNAzymes, have shown promise as a therapeutic intervention against cancer in various in vitro and in vivo models, expediting towards clinical applications. DNAzymes are single-stranded catalytic DNA that has not been observed in nature, and they are synthesized through in vitro selection processes from a large pool of random DNA libraries. The intrinsic properties of DNAzymes like small molecular weight, higher stability, excellent programmability, diversity, and low cost have brought them to the forefront of the nucleic acid-based therapeutic arsenal available for cancers. In recent years, considerable efforts have been undertaken to assess a variety of DNAzymes against different cancers. However, their therapeutic application is constrained by the low delivery efficiency, cellular uptake, and target detection within the tumour microenvironment. Thus, there is a pursuit to identify efficient delivery methods in vivo before the full potential of DNAzymes in cancer therapy is realized. In this light, a review of the recent advances in the use of DNAzymes against cancers in preclinical and clinical settings is valuable to understand its potential as effective cancer therapy. We have thus sought to firstly provide a brief overview of construction and recent improvements in the design of DNAzymes. Secondly, this review stipulates the efficacy, safety, and tolerability of DNAzymes developed against major hallmarks of cancers tested in preclinical and clinical settings. Lastly, the recent advances in DNAzyme delivery systems along with the challenges and prospects for the clinical application of DNAzymes as cancer therapy are also discussed.